Accuracy of Linear Measurements of Galileos Cone Beam Computed Tomography in Normal and Different Head Positions. (16th July 2012) - Sheikhi, Mahnaz; Ghorbanizadeh, Sajad; Abdinian, Mehrdad; Goroohi, Hossein; Badrian, Hamid
Abstract : Introduction . The aim of this study was to determine the accuracy of linear measurements in dry human skulls in ideal position and different deviated positions of the skull. Methods . 6 dry human skulls were included in the study. Opaque markers were attached to alveolar bone. Buccolingual and mesiodistal distances and heights were measured in 5 different regions of either jaws using a digital caliper. Radiographic distances were measured in ideal, rotation, tilt, flexion, and extension positions of the skulls. The physical and radiographic measurements were compared to estimate linear measurement accuracy. Results . The mean difference between physical measurements and radiographic measurements was 0.05 ± 0.45 . There was a significant difference between physical measurements and radiographic measurements in ideal, rotation, tilt, and extension positions (P value < 0.05 ). Conclusions . The accuracy of measurements in GALILEOUS CBCT machine varies when the position of the skull deviates from ideal; however, the differences are not clinically significant.